Resilient And Sustainable HR Systems: The Work-From-Anywhere (WFA)–Organizational Citizenship Behavior (OCB) Nexus In Indonesia’s Public Sector - Andi Rahmawati; Muhammad Rijal Alim Rahmat (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The adoption of Work-From-Anywhere (WFA) arrangements in Indonesia’s public sector has generated important questions regarding their implications for Organizational Citizenship Behavior (OCB), which remains essential for public service effectiveness. This qualitative single-case study examines the relationship between WFA and OCB within a provincial development planning agency in South Sulawesi. Using the Framework Method, data were triangulated from role-segmented semi-structured interviews, non-participant observations of hybrid and online coordination meetings, and analysis of internal organizational documents. The findings indicate that WFA does not inherently diminish OCB. Instead, citizenship behaviors—particularly helping, courtesy, and conscientiousness—were sustained and, in some organizational units, strengthened when supported by three interrelated enablers: transparent visibility mechanisms, structured communication cadence, and fair allocation of WFA eligibility. Increased autonomy under WFA was frequently associated with enhanced self-discipline and discretionary effort, while trust-based leadership and perceptions of procedural justice reinforced employees’ willingness to contribute beyond formal role requirements. Conversely, unclear eligibility criteria, weak coordination routines, excessive administrative procedures, and uneven digital infrastructure were associated with reduced OCB signals and coordination challenges. The study concludes that the impact of WFA on OCB in the public sector is contingent upon organizational design and leadership practices rather than the flexibility policy itself. These findings offer practical guidance for human resource policy design in public administration and contribute to broader discussions on resilient and sustainable public-sector workforce systems.